2015
DOI: 10.1186/s12906-015-0903-1
|View full text |Cite
|
Sign up to set email alerts
|

A new prognostic scale for the early prediction of ischemic stroke recovery mainly based on traditional Chinese medicine symptoms and NIHSS score: a retrospective cohort study

Abstract: BackgroundIschemic stroke (IS) is a common disease, often resulting in death or disability. Previous studies on prognosis of stroke mainly focused on the baseline condition or modern expensive tests. However, the change of clinical symptoms during acute stage is considerably neglected. In our study, we aim to develop a new prognostic scale to predict the 90-day outcome of IS patients.MethodsIn this retrospective cohort study, a secondary data analysis was performed on 489 patients extracted from 1046 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The YD pattern was associated with paleness, a red zygomatic site and dry mouth. These results were similar to other studies presented by our team and other TCM researchers 13 14 .…”
Section: Discussionsupporting
confidence: 93%
“…The YD pattern was associated with paleness, a red zygomatic site and dry mouth. These results were similar to other studies presented by our team and other TCM researchers 13 14 .…”
Section: Discussionsupporting
confidence: 93%
“…For instance, gurgling with sputum, which is a reflection of phlegm syndrome, might be a factor affecting the recovery of motor dysfunction. A previous study [7] used the Pearson correlation test and logistic regression model to review 489 patients with acute ischemic stroke and finally screened eight items of the scale, indicating that early appearance of anxiety might predict a bad outcome at the ninetieth (90 th ) day (OR: 3.17). Our study observed the recovery of motor function at the first year, which was much longer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current evidence showed the performance evaluation of TCM scales is uneven [6]. Scales in general accepted standards have not been applied as early predictive indicators of stroke outcome in the prognostic scale [7]. Typically, some early prognostic symptoms are important for the development of precision medicine, quality of life, and prognosis of stroke, which need to be testified in the progress of medical practice.…”
Section: Introductionmentioning
confidence: 99%
“…exceeded the forecasts of experienced doctors [33]. Changes in the health status assessment of health status in the framework of traditional Chinese medicine during the first 5 days after a stroke predicted a 90-day course of the disease [34]. As motor functions and movement are generally at the heart of the rehabilitation process, several studies have focused on predicting the recovery of these functions and special models have been created for this application [35].…”
Section: Discussionmentioning
confidence: 99%